Low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer and preparation method of low-iridium oxygen evolution membrane electrode

By using a preformed porous metal conductive thin layer supported by iridium or ruthenium-based catalyst in a proton exchange membrane water electrolyzer, the problems of insufficient conductivity of the catalytic layer and low iridium utilization are solved, and a high-efficiency low-iridium film electrode is achieved, reducing the Cost and improve water and gas transmission capacity.

CN119194507APending Publication Date: 2024-12-27GUANGZHOU INST OF ENERGY CONVERSION CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411393626.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

After reducing the amount of iridium, existing proton exchange membrane water electrolytics face problems such as insufficient catalytic layer conductivity, low iridium utilization rate and high water and gas transmission resistance, which is difficult to meet the needs of large-scale applications.

Method used

A preformed porous metal conductive thin layer is used as the basis of the catalytic layer, and the surface is supported by chemical deposition or ink spraying to form an efficient low-iridium oxygen evolution film electrode to enhance the conductivity of the catalytic layer and iridium. utilization rate.

Benefits of technology

High-performance membrane electrodes under low iridium load are achieved, which improves the overall efficiency of the electrode and the utilization rate of iridium, reduces costs, and ensures efficient water and gas transmission capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194507A_ABST
    Figure CN119194507A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: firstly, obtaining a porous metal conductive thin layer by adopting a metal powder pre-forming strategy, constructing a conductive layer network through tightly connected metal particles, enhancing the conductivity of a catalytic layer, and carrying out a rear noble metal loading process to obtain the low-iridium oxygen evolution membrane electrode for the proton exchange membrane water electrolyzer. Precious metal is enriched on the surface of the porous metal conductive thin layer, the characteristics of high diaphragm-oriented iridium loading capacity and low diaphragm-far loading capacity are formed, the problem that rear-layer catalyst active ingredients far away from a proton exchange membrane in a catalyst layer are difficult to utilize is solved, and the utilization rate of iridium is increased conveniently. In addition, the thickness of the prepared porous metal conductive thin layer is thinner and more uniform than that of an existing catalyst layer, a proton conductive polymer can not be used, meanwhile, the efficient water vapor transmission capacity is guaranteed, the overall efficiency of a membrane electrode is improved, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the technical field of green hydrogen production and carbon emission reduction, and in particular to a low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer and a preparation method thereof. Background technology:

[0002] Hydrogen production by water electrolysis is a very important low-carbon hydrogen production technology route. Among them, solid polymer water electrolysis hydrogen production technology has attracted much attention due to its advantages of high current density, high hydrogen production efficiency, and strong adaptability to renewable energy systems. However, solid polymer water electrolyzers, especially the more mature proton exchange membrane water electrolyzers (PEMWE), still face the problem of high costs. In order to meet the conditions for large-scale application, greatly reducing the amount of precious metals in membrane electrodes, especially iridium, is the current research focus.

[0003] Current proton exchange membrane water electrolyzers (PEMWEs) require extremely high iridium dosages (1.5-3 mg cm) when using unsupported iridium-based catalysts to ensure electrode performance. -2 ), which greatly increases the cost of membrane electrode. However, after reducing the loading, the proton exchange membrane water electrolyzer faces the problem of reduced hydrogen production efficiency and poor stability. In order to improve the performance of low iridium membrane electrode, researchers used oxides as carriers to load iridium to prepare composite catalysts, and then enhanced the performance of water electrolyzers by improving the dispersion of iridium. However, this type of process still faces several key constraints: (1) The problem of insufficient conductivity of oxide carriers and catalyst layers; the generally used oxide carriers have insufficient electronic conductivity, resulting in low utilization of iridium catalysts. At the same time, the catalyst layer is composed of catalysts and non-conductive binders, and the conductivity will be further reduced, thereby increasing resistance polarization (2) The dispersion and utilization of iridium in the catalyst layer are not high; the iridium distribution in the catalyst layer obtained by using composite catalysts is relatively uniform, which will lead to the length of the catalyst proton diffusion path away from the membrane, causing a decrease in utilization (3) The problem of increased water and gas transmission resistance after the introduction of the carrier. Therefore, although this type of technology reduces the iridium loading to a certain extent, it still cannot meet the current actual needs. Therefore, how to effectively solve the problems of insufficient conductivity, low utilization of iridium catalysts and high water and gas transmission resistance at the same time is the key to be solved urgently. Summary of the invention:

[0004] The purpose of the present invention is to provide a low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer and a preparation method thereof, which solves the problems of poor electron conductivity of the catalytic layer of the low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer in the prior art and low utilization rate of the precious metal iridium in the back layer.

[0005] The present invention is achieved through the following technical solutions:

[0006] A low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer, wherein the catalytic layer is composed of a preformed porous metal conductive thin layer and an iridium-based and / or ruthenium-based catalyst loaded on the surface thereof, wherein the preformed porous metal conductive thin layer is formed by coating or spraying acid-corrosion-resistant metal powder and a binder on the surface of a polytetrafluoroethylene film and then drying; the iridium-based or ruthenium-based catalyst is a metal or metal oxide or metal hydroxide of iridium or ruthenium, with a particle size of 1 to 50 nm and an iridium or ruthenium loading of 0.04 to 0.2 mg / cm -2 , preferably 0.04-0.1mgcm -2 .

[0007] The thickness of the porous metal conductive thin layer is 0.1-10 μm, preferably 0.5-3 μm.

[0008] The metal powder is one or a combination of gold, titanium and niobium, and the particle size of the metal powder is 0.06-5 μm, preferably 0.3-2 μm.

[0009] The binder is polytetrafluoroethylene or perfluorosulfonic acid resin, and the content of the binder is 1%-20%.

[0010] The iridium-based and ruthenium-based catalysts are loaded in chemical deposition, electrodeposition, impregnation reduction, impregnation sintering, and ink spraying methods.

[0011] The method for preparing the low-iridium oxygen evolution membrane electrode for the proton exchange membrane water electrolyzer comprises the following steps:

[0012] (1) Preforming a porous metal conductive thin layer: mixing metal powder with water and ethanol, then adding a binder, wherein the binder content is 1% to 20%, and mixing evenly by ultrasonic stirring to obtain a metal powder mixed solution; coating or spraying the metal powder mixed solution on the surface of the polytetrafluoroethylene film, controlling the thickness of the thin layer by adjusting the coating amount of the metal powder mixed solution, and then drying to form a porous metal conductive thin layer;

[0013] (2) placing the porous metal conductive thin layer coated on the surface of the tetrafluoroethylene film obtained in step (1) in a chloroiridic acid or / and ruthenium trichloride precursor solution, and then forming an iridium-based and / or ruthenium-based metal or metal oxide or metal hydroxide on the surface of the porous metal conductive thin layer by chemical deposition or electrochemical deposition or impregnation reduction or impregnation sintering to obtain a porous metal conductive thin layer loaded with an iridium-based and / or ruthenium-based catalyst;

[0014] Or, by preparing iridium oxide and / or ruthenium oxide ink, and spraying the ink onto the surface of the porous metal conductive thin layer coated on the surface of the tetrafluoroethylene film to achieve loading;

[0015] (3) The porous metal conductive thin layer loaded with iridium-based and / or ruthenium-based catalyst obtained in step (2) is transferred to the surface of the proton exchange membrane by a transfer method to form a low-iridium anode.

[0016] The present invention advances the forming step of the catalytic layer to before the loading of the catalyst active components, that is, the metal powder is pre-formed into a porous metal conductive thin layer to first construct a continuous electron conduction path and enhance the conductivity of the catalytic layer. Subsequently, the pre-obtained porous layer is brought into single-sided contact with the catalyst precursor to achieve iridium enrichment on the surface of the porous metal conductive thin layer, which is beneficial to improving the overall efficiency of the membrane electrode and solves the problem that the catalyst active components in the rear layer of the catalytic layer far away from the proton exchange membrane are difficult to be utilized.

[0017] The beneficial effects of the present invention are as follows:

[0018] 1) The present invention adopts a metal powder pre-forming strategy to construct a porous metal conductive thin layer. The porous metal conductive thin layer is formed by tightly connecting metal powders. The metal-metal interface can enhance electron transmission and has stronger conductivity, thereby achieving high performance at a low iridium loading.

[0019] 2) The present invention places the catalyst active component loading process at a later stage, which is beneficial for the catalyst precursor to enter the hydrophilic region of the porous metal conductive thin layer rather than the hydrophobic region, thereby avoiding the deactivation of the iridium catalyst in the hydrophobic region due to lack of water, thereby improving the utilization rate of the active components of the water electrolysis catalyst and the electrode performance.

[0020] 3) The present invention achieves iridium enrichment on the surface of the porous metal conductive thin layer by means of single-sided contact with the catalyst precursor, resulting in a high loading facing the diaphragm and a low loading away from the diaphragm, thereby improving the utilization rate of iridium.

[0021] 4) The thickness of the porous metal conductive thin layer of the present invention is thinner and more uniform than that of the existing catalytic layer, and proton conductive polymers do not need to be used. At the same time, efficient water vapor transmission capacity is guaranteed, which is beneficial to improving the overall efficiency of the membrane electrode and reducing costs.

[0022] In short, the present invention uses metal powder to pre-form a porous metal conductive thin layer to first construct a conductive layer, strengthen the conductivity of the catalyst layer, and the prepared electrode has a higher conductivity than the traditional catalyst layer, which is conducive to solving the catalyst deactivation caused by the poor electronic conductivity of the low iridium electrode. Subsequently, the iridium-based and / or ruthenium-based precious metal active components are loaded on the conductive layer to achieve surface enrichment of iridium on the porous metal conductive thin layer, forming a high iridium loading facing the diaphragm and a low loading away from the diaphragm, which can improve the utilization rate of iridium. The problem that the active components of the rear catalyst layer away from the proton exchange membrane in the catalyst layer are difficult to be utilized is solved. In addition, the thickness of the prepared porous metal conductive thin layer is thinner and more uniform than the existing catalyst layer, and proton conductive polymers can be omitted, while ensuring efficient water vapor transmission capacity, which is conducive to improving the overall efficiency of the membrane electrode and reducing costs. Description of the drawings:

[0023] Figure 1 is a schematic diagram of the preparation process of Example 1;

[0024] Figure 2 is an electron microscope image of the morphology of the electrode catalyst layer obtained in Example 1;

[0025] Figure 3 is the iridium distribution curve of the catalyst layer obtained in Example 1;

[0026] Figure 4 This is the water electrolysis polarization curve of the membrane electrode prepared in Example 1. Specific implementation method:

[0027] The following is a further description of the present invention, rather than a limitation of the present invention.

[0028] Example 1: A low-iridium film electrode and its preparation method

[0029] Prepared by the following steps:

[0030] (1) Mix titanium powder with a particle size of 200 nm with water and ethanol (the mass ratio of water to ethanol is 1:5) to a solid-liquid ratio of 20:1, and disperse by ultrasound for 30 minutes. Then add a 60% polytetrafluoroethylene solution as a binder with a content of 2%, and disperse by ultrasound for 30 minutes to obtain ink;

[0031] (2) 5 ml of the ink obtained in step (1) was coated on the surface of a 20 μm thick polytetrafluoroethylene film and dried at 80 degrees to obtain a porous conductive thin layer with a thickness of 0.6 μm.

[0032] (3) The iridium-based precursor solution is a 20 mmol / L aqueous solution of chloroiridic acid, and the loading process adopts a chemical deposition method. The porous thin layer attached to the surface of the film obtained in step (2) is contacted with the iridium-based solution, and then a sodium hypochlorite solution with a concentration of 10 mmol / L is added, and the mixture is allowed to stand at room temperature for 12 hours to obtain a catalyst layer loaded with iridium oxide on the surface, wherein the iridium oxide particle size is 1 nm, and the iridium loading in the catalyst layer is 0.09 mg / cm -2 .

[0033] (4) The catalyst layer obtained in step (3) is combined with the Nafion 117 membrane by a transfer method. The hot pressing temperature is 150 degrees and the pressure is 6 MPa. After hot pressing for 5 minutes, a low iridium membrane electrode is formed.

[0034] The loading amount of iridium oxide was determined by X-ray fluorescence spectroscopy, and the surface resistance of the electrode was measured by the four-probe method at room temperature. The electrochemical active area of ​​a single cell of the water electrolyzer is 8 cm 2The cathode catalyst is a traditional platinum-carbon catalyst with a platinum loading of 0.1 mg cm -2 The solid polymer membrane is Nafion 117 membrane. The single tank performance test was carried out at 80°C and normal pressure.

[0035] Figure 2 This is an electron microscope image of the electrode prepared in this example. Figure 3 The distribution curve of iridium in the cross section of the catalyst layer. It can be seen that after the process of pre-forming and loading iridium, the distribution of iridium shows a distribution characteristic of high loading on the side facing the membrane and low loading on the side away from the membrane. The surface resistance measured by the four-probe method is 25Ωcm -2 .

[0036] Figure 4 This is the membrane electrode polarization curve obtained in Example 1. When the iridium loading is only 0.09 mg cm -2 When , the water electrolyzer can achieve a cell voltage of 1.732V, showing extremely high activity.

[0037] Comparative Example 1

[0038] Reference Example 1, the difference from Example 1 is: commercially available iridium oxide powder is uniformly mixed with water and ethanol, with a solid-liquid ratio of 20:1, and then ultrasonically dispersed for 30 minutes. After adding 5% Nafion solution, it is coated on the surface of a 20-micron thick polytetrafluoroethylene film, wherein the Nafion content is 5%. After drying at 80 degrees, it is transferred to the surface of the Nafion117 membrane. The coating process, transfer process, iridium loading and test conditions are exactly the same as those in Example 1.

[0039] The surface resistance measured by the four-probe method is 84 kΩcm -2 The single-cell test showed that the membrane 1A / cm 2 The voltage of the lower single cell is 1.829 V, which is higher than the cell voltage of Example 1, indicating that the energy consumption of hydrogen production is high.

[0040] Example 2

[0041] This embodiment refers to the embodiment 1, and the difference from the embodiment 1 is that: in step (1), gold powder with a particle size of 60nm is used, and the content of polytetrafluoroethylene is 1%. In step (2), 1.5ml of ink is taken, and the thickness of the conductive layer formed is 0.1μm. In step (3), the standing time is 1 hour, the particle size of the iridium oxide obtained is 1.5nm, and the iridium loading in the catalyst layer is 0.04mgcm -2 The remaining steps and test methods are exactly the same as those in Example 1.

[0042] The surface resistance measured by the four-probe method is 14Ωcm -2 The single tank test shows that the water electrolyzer membrane electrode 1A / cm 2The voltage of the lower single slot is 1.707V.

[0043] Example 3

[0044] This example refers to Example 1, and the difference from Example 1 is that the powder in step (1) is metal niobium powder with a particle size of 5 μm. In step (2), 7 ml of the prepared ink is taken and the conductive layer formed by coating is 10 μm thick. In step (3), the iridium oxide particle size is 2 nm, and the iridium loading in the catalyst layer is 0.2 mg cm -2

[0045] The surface resistance measured by the four-probe method is 104Ωcm -2 The single tank test shows that the water electrolyzer membrane electrode 1A / cm 2 The voltage of the lower single slot is 1.729V.

[0046] Example 4

[0047] This embodiment refers to the embodiment 1, and the difference from the embodiment 1 is that: in step (1), gold and titanium powders are mixed in a mass ratio of 1:1, and a binder is a 5% perfluorosulfonic acid resin solution with a content of 20%. In step (3), an electrodeposition method is used, and the operation is carried out for 400 seconds under the condition of 1.2V (vs.RHE), and the obtained iridium oxide particle size is 50nm.

[0048] The surface resistance measured by the four-probe method is 1749Ωcm -2 The single tank test shows that the water electrolyzer membrane electrode 1A / cm 2 The voltage of the lower single slot is 1.708V.

[0049] Example 5

[0050] This embodiment refers to the embodiment 1, and the difference from the embodiment 1 is that: in step (1), gold, titanium and niobium powders are mixed in a mass ratio of 1:1:0.5. In step (3), a 50 mmol / L ruthenium chloride aqueous solution is used as a precursor, and an immersion reduction method is adopted. After the porous layer is impregnated, it is taken out and dried at 80 degrees, and then reduced at 200 degrees for 30 minutes in a 5% hydrogen-argon mixed atmosphere.

[0051] The surface resistance measured by the four-probe method is 454Ωcm -2 The single tank test shows that the water electrolyzer membrane electrode 1A / cm 2 The voltage of the lower single slot is 1.741V.

[0052] Example 6

[0053] This embodiment refers to the embodiment 1, and the difference from the embodiment 1 is that: step (3) uses an aqueous solution of 50mmol / L chloroiridic acid and ruthenium trichloride as a precursor, wherein the molar ratio of iridium to ruthenium is 7:3. The porous layer is taken out and dried at 80°C after being immersed in the precursor by the immersion sintering method, and then heat-treated at 250°C for 30 minutes in an air atmosphere.

[0054] The surface resistance measured by the four-probe method is 256Ωcm -2 The single tank test shows that the water electrolyzer membrane electrode 1A / cm 2 The voltage of the lower single slot is 1.715V.

[0055] Example 7

[0056] This embodiment refers to Example 1, and the difference from Example 1 is that: in step (3), commercially available iridium oxide powder is uniformly mixed with water and ethanol, with a solid-liquid ratio of 20:1, and then ultrasonically dispersed for 30 minutes. After adding 5% Nafion solution, stir for 30 minutes, wherein the Nafion content is 5%. Then, the ink is sprayed on the surface of the porous metal layer obtained in step (2) using a spray gun, and dried at 80 degrees to obtain a catalyst layer with iridium oxide on the surface. The remaining iridium loading, transfer process and test conditions are exactly the same as those in Example 1.

[0057] The surface resistance of the membrane electrode sprayed with iridium oxide was measured by four-probe method and was 196Ωcm -2 The single tank test shows that the water electrolyzer membrane electrode 1A / cm 2 The voltage of the lower single cell is 1.725 V. The surface resistance of the membrane electrode sprayed with ruthenium oxide ink is Ωcm -2 , water electrolyzer membrane electrode 1A / cm 2 The voltage of the lower single slot is 1.686V.

Claims

1. A low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer, characterized in that: The catalytic layer is composed of a preformed porous metal conductive thin layer and an iridium-based and / or ruthenium-based catalyst loaded on the surface thereof. The preformed porous metal conductive thin layer is formed by coating or spraying acid-corrosion-resistant metal powder and a binder on the surface of a polytetrafluoroethylene film and then drying. The iridium-based and ruthenium-based catalysts are metals or metal oxides or metal hydroxides of iridium or ruthenium, with a particle size of 1 to 50 nm and an iridium or ruthenium loading of 0.04 to 0.2 mg / cm -2 .

2. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: Iridium or ruthenium loading is 0.04-0.1mgcm -2 .

3. The low iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The metal powder is one or a combination of gold, titanium and niobium, and the particle size of the metal powder is 0.06-5 μm.

4. The low iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 3, characterized in that: The particle size of the metal powder is 0.3-2 μm.

5. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The binder is polytetrafluoroethylene or perfluorosulfonic acid resin, and the content of the binder is 1%-20%.

6. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The iridium-based and ruthenium-based catalysts are loaded in chemical deposition, electrodeposition, impregnation reduction, impregnation sintering, and ink spraying methods.

7. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The thickness of the porous metal conductive thin layer is 0.1-10 μm.

8. A method for preparing a low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer according to claim 1, characterized in that: The following steps are involved: (1): Mix metal powder with water and ethanol, then add a binder, wherein the binder content is 1% to 20%, and mix evenly by ultrasonic stirring to obtain a metal powder mixed solution; use a coating or spraying process to cover the metal powder mixed solution on the surface of the polytetrafluoroethylene film, control the thickness of the thin layer by adjusting the coating amount of the metal powder mixed solution, and then dry to form a porous metal conductive thin layer; (2) placing the porous metal conductive thin layer coated on the surface of the tetrafluoroethylene film obtained in step (1) in a chloroiridic acid or / and ruthenium trichloride precursor solution, and then forming an iridium-based and / or ruthenium-based metal or metal oxide or metal hydroxide on the surface of the porous metal conductive thin layer by chemical deposition or electrochemical deposition or impregnation reduction or impregnation sintering to obtain a porous metal conductive thin layer loaded with an iridium-based and / or ruthenium-based catalyst; Or, by preparing iridium oxide and / or ruthenium oxide ink, and spraying the ink onto the surface of the porous metal conductive thin layer coated on the surface of the tetrafluoroethylene film to achieve loading; (3) The porous metal conductive thin layer loaded with iridium-based and / or ruthenium-based catalyst obtained in step (2) is transferred to the surface of the proton exchange membrane by a transfer method to form a low-iridium anode.

9. The preparation method according to claim 7, characterized in that: The metal powder is one or a combination of gold, titanium and niobium, and the particle size of the metal powder is 0.06-5 μm; the binder is polytetrafluoroethylene or perfluorosulfonic acid resin.

10. The preparation method according to claim 7, characterized in that: The thickness of the porous metal conductive thin layer is 0.1-10 μm.

Citation Information

Cited By

  • Electrode with mixed metal oxide particles embedded in a plastic matrix and having a partial exposed finish, and method for the production thereof

    EP4768447A1